2006
DOI: 10.1299/jsmea.49.376
|View full text |Cite
|
Sign up to set email alerts
|

High Space-Resolutive Evaluation of Subsurface Stress Distribution by Strain Scanning Method with Analyzer Using High-Energy Synchrotron X-Rays

Abstract: The surface aberration effect in the strain scanning method with a Ge analyzer was examined using high-energy X-rays from the undulator synchrotron source. The synchrotron X-rays from the undulator source had an enough intensity for the strain scanning method using a goniometer with the analyzer. The use of a Ge (111) analyzer showed remarkable reduction of the surface aberration effect. However, there still existed the surface aberration for the very-near surface region from the surface to the depth of 50 µm.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 5 publications
0
2
0
Order By: Relevance
“…Above 1 ps, as the pulse duration increased, the crater depth decreased and the melted region widened around the irradiated area, which suggested that thermal effects, such as heat diffusion, dominated over the shock effects. 30 Below 1 ps, as the pulse duration decreased, the crater depth decreased and the irradiated area increased, which suggested a decrease in the laser fluence. Drogoff et al and Nielsen et al reported that for an ultrashort pulsed laser with a pulse duration below 1 ps, the amount of ablation was less dependent on the pulse durations.…”
Section: A Effects Of Optical Nonlinear Phenomenamentioning
confidence: 99%
See 1 more Smart Citation
“…Above 1 ps, as the pulse duration increased, the crater depth decreased and the melted region widened around the irradiated area, which suggested that thermal effects, such as heat diffusion, dominated over the shock effects. 30 Below 1 ps, as the pulse duration decreased, the crater depth decreased and the irradiated area increased, which suggested a decrease in the laser fluence. Drogoff et al and Nielsen et al reported that for an ultrashort pulsed laser with a pulse duration below 1 ps, the amount of ablation was less dependent on the pulse durations.…”
Section: A Effects Of Optical Nonlinear Phenomenamentioning
confidence: 99%
“…2. 30 The diffracted x rays were detected using a CdTe detector. The size of the incident and receiving slits were 200 μm in the horizontal direction and 5 μm in the vertical direction.…”
Section: G Dislocation Densitymentioning
confidence: 99%